Effectiveness of growing catfish (Clarias gariepenus) using feed with chicken manure substitution - Puteri, Rizki Eka; Saadah, Raudhatus; Guttifera, Guttifera; Lestari, Siti; Rizki, Rani Ria; Prariska, Donny; Sari, Selly Ratna; Rarassari, Madyasta Anggana; Khairunisa, Eka Nurriza (Program Studi Akuakultur, Fakultas Pertanian, Universitas Almuslim, 2024)
Catfish is a fish that is currently in great demand among Indonesian people. Catfish are nocturnal fish that are active at night and are also omnivorous or eat everything. Catfish is a fish that can consume food from plants such as vegetables and trash fish as well as other food ingredients, one of which is chicken manure. The nutritional content of chicken manure can be substituted in making catfish feed so that the use of chicken manure for fish feed can be done. In this study, 4 treatments were made with 3 repetitions, namely A1 (control), A2 (10%), A3 (15%) and A4 (20%). The highest protein content was obtained in treatment A4 (20%) with a value of 32.40%. The best daily growth results were obtained in treatment A2 (10%) which was 3.80 cm and was the highest value compared to the daily growth value in the control. The best survival rate results were obtained in treatment A3 (15%), namely 99.33%. The best feed efficiency was obtained in treatment A2 (10%), namely 97.70% and the highest survival value was obtained in this treatment. From the results of the research that has been carried out, it was found that the best treatment is the use of chicken manure in treatment A2, namely the use of 10% manure in additional feed for catfish farming fish, so that the use of 10% chicken manure in 1 kg of feed can increase growth and feed efficiency in fish farming catfish.